Education in the opinion of al-Qabesi (Journal of the College of Basic Education, 2022)
The subject of education is of great importance in all ages and nations, and scholars and philosophers have taken care of it, so they wrote treatises and books on it, long ago, and it is still the subject of interest of thinkers and reformers.